Pengalaman kelangsungan hidup wanita dalam perkahwinan jarak jauh / Norsafatul Aznin A. Razak - Norsafatul Aznin, A. Razak (2016)
This study was conducted to explore in depth about the experiences of women's survival in long-distance marriages. Seven women in such marriages were interviewed using a transcendental-phenomenological qualitative design. Data were collected using semi-structured interviews with each participants interviewed three times. A total of 21 interview sessions were obtained with each interview lasting between 40 to 90 minutes. Data analysis was done using the phenomenological method assisted by software of Atlas.ti. version 7 . The issues of validity and reliability were obtained through Audit Trail, detailed description and member checking processes. The study revealed seven major themes that represent the essence of the experiences of women’s survival in long distance marriages. These seven themes of women’s survival experiences are divided into four main stages of long distance marriages. The first theme is related to "contributing factor" representing the planning stage. These contributory factors are like economic, family, career and environmental factors. The second theme called “reunion-separation cycle” which is related to psychological responses. Then, the third theme which is "dynamic of relationship” that includes nuclear and multigenerational relationships, and the fourth theme of "family system" which refers to the child and the family included in the exploration and preparation stage. Next, the fifth theme called "survival mechanism" which lead to intrinsic and extrinsic mechanism, the sixth theme called "support system" that involved family members and non-family members supports, and the "development of resilience" iv theme representing the implementation and development stage in long distance marriages. Overall, the stages in the cycle of long distance marriage that became the essence of the experience of the women’s survival are linked and interrelated to one another. So, the outcome of this study could assist the practitioners of counseling to understand deeper and provide a new paradigm about the meaning of survival experiences of women in long distance marriages. Furthermore, from the data obtained, this study discussed implications on the couples and family counselors in planning and implementing the most appropriate interventions to cope with the issues of long distance marriages counseling. The implication on socialization is also obtained through planning of the implementation of pre-marriage and parenting modules for individuals and couples who are involved in long-distance marriages. Because the study is conducted on Malay women only, future research can explore in more detail about the husband and children’s perspectives from various cultural backgrounds. Finally, the result of this study also discovered the emergence of a new theme that is the spiritual aspect which plays an important role in long-distance marriage. Thus, in depth exploration of this aspect is something that can be taken up by future researchers.